An energy-efficient method of laser remanufacturing process. (August 2022) - Jiang, Xingyu; Tian, Zhiqiang; Liu, Weijun; Tian, Guangdong; Gao, Yun; Xing, Fei; Suo, Yingqi; Song, Boxue
Abstract: With the global energy shortages and the increasing concerns of environmental protection in various countries, energy consumption optimization in laser remanufacturing has attracted much attention. To address the problems of large energy consumption and high cost in the laser remanufacturing process, the energy consumption characteristics and mechanism of the laser remanufacturing process are analyzed in this work. Then an energy consumption model of the laser remanufacturing process is established. Moreover, an optimization model of laser remanufacturing process parameters with objectives of energy consumption, powder utilization rate, hardness and aspect ratio is formulated. A novel non-dominated sorting genetic algorithm-II (NSGA-II) based on adaptive crossover probability and multi-crossover operators is proposed to solve the model. In this way, the optimal process parameters are obtained by the improved Technique for Order Preference by Similarity to an Ideal Solution (TOPSIS) method. Finally, some remanufacturing experiments are carried out on the LDM4030 laser remanufacturing equipment. The results show that the model and algorithm presented in this work can effectively reduce energy consumption, improve powder utilization rate and ensure the quality of cladding. The research results of this work can provide an effective way for an energy-efficient laser remanufacturing process and give reference to the energy consumption optimization of other laser surface engineering technologies, such as laser shock strengthening and laser cleaning.